On Semi- regular T1 and Semi- regular T2 in Intuitionistic Fuzzy Topological Spaces - Fatimah M. Mohammed (Tikrit Journal of Pure Science, 2023)
The purpose of this paper is to give the new definitions of semi-regular T1 and semi-regular T2 separation axioms in intuitionistic fuzzy topological spaces. Study the basic properties, characterizations and relationships of these new concepts in intuitionistic fuzzy topological spaces.